Knowledge, attitude, and practice towards thyroid nodules and cancer among patients: a cross-sectional study - Li, Wei; Deng, Jian; Xiong, Wei; Zhong, Yangyan; Cao, Hong; Jiang, Guoqin (Frontiers in Public Health, 2023)
Aim: This study aimed to explore the knowledge, attitude, and practice (KAP) towards thyroid nodules (TN) and thyroid cancer (TC) among patients. Subject and Methods: This cross-sectional study enrolled patients with TN or TC at the Second Affiliated Hospital of the University of South China between September 2022 and February 2023. A self-administered questionnaire was developed to collect demographic information of the participants, and their knowledge, attitude and practice (KAP) towards TN and TC. Results: A total of 510 valid questionnaires were collected. Among the participants, 102 (20.00%) were male, and 197 (38.63%) had the diagnosis of TC. The knowledge, attitude and practice scores were 5.76 ± 3.09 (possible range: 0-12), 31.07 ± 2.73 (possible range: 9-45), and 18.97 ± 2.92 (possible range: 5-25), respectively. Multivariate logistic regression showed that age of above 50 years old (OR = 0.27, 95%CI: 0.12-0.64, P = 0.003), junior college or bachelor’s degree and above (OR = 4.97, 95%CI: 1.74-14.20, P = 0.003), monthly income of 5000-10000 CNY (OR = 2.02, 95%CI: 1.09-3.74, P = 0.025) and > 10000 CNY (OR = 5.67, 95%CI: 2.49-12.94, P < 0.001) were independently associated with knowledge. The good knowledge (OR = 3.87, 95%CI: 1.89-7.95, P < 0.001), high school or technical secondary school (OR = 0.52, 95%CI: 0.30-0.88, P = 0.016), and monthly income of 5000-10000 CNY (OR = 2.02, 95%CI: 1.13-3.63, P = 0.018) were independently associated with practice. Conclusion: Patients demonstrated poor knowledge, moderate attitude, and proactive practice towards TN and TC.